Keberlangsungan Dukungan Keluarga Dengan Peningkatan Pengobatan Tbc Di Uptd Puskesmas Langkahan - Riansyah, Ferdi; Ramadana, Vintary Sari; Farida, Elly Kartika; Fajriansyah, Fajriansyah (Teewan Solutions, 2025)
Tuberculosis disease has been known more than a century ago, since the discovery of the germ that causes Tuberculosis by Robert Koch in 1882. However, Tuberculosis (TB) is still a health problem worldwide and is the leading cause of death caused by infectious diseases. WHO in 1993 said that TB is a very important and serious public health poblema around the world and is a disease that causes a global emergency, because one in three people in the world is estimated to have been infected with Mycobacterium tuberculosis (also called Acid-Resistant Bacillus = BTA) as the germ that causes TB as evidenced by the Mantouxtes examination. Geographically, the most TB cases are in Southeast Asia (45.6%), Africa (23.3%) and Western Pacific (17.8%), and the smallest in the Eastern Mediterranean (8.1%), The Americas (2.9%) and Europe (2.2%). This study uses a quantitative approach, by formulating a hypothesis which is then carried out statistical testing to accept or reject the hypothesis. This study aims to determine the relationship between family support and treatment adherence in tuberculosis patients. Based on the table above on instrumental support, it shows that less instrumental support (10%) in non-compliant patients is lower than good instrumental support (57.1%). Based on statistical tests, the p-value of instrumental support is 0.001 which means there is a meaningful relationship between instrumental support and tuberculosis treatment adherence.